Air Quality Measurement System - Fuxa, Dominik (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
In our project, we are interested air quality in region of Brno. We measure it with gas sensors placed on the drone. We record the results on a heat map. On this project, I work together with my friend Jana Lázničková. I am in charge of communications and she is concerned with data acquisition and processing.
Keywords: LoraWan; guide